An observational study of the use of beclomethasone dipropionate suppositories in the treatment of lower urinary tract inflammation in men. Issue 1 (December 2016) - Bozzini, Giorgio; Provenzano, Marco; Buffi, Nicolò; Seveso, Mauro; Lughezzani, Giovanni; Guazzoni, Giorgio; Mandressi, Alberto; Taverna, Gianluigi
Abstract Background Nonbacterial prostatitis, together with chronic pelvic pain syndrome, accounts for 90–95 % of prostatitis cases. Anti-inflammatory medications are commonly used to reduce storage/inflammatory symptoms that can deteriorate quality of life. The purpose of this study was to observe the efficacy and safety of beclomethasone dipropionate rectal suppositories (Topster®) in inflammations of the lower urinary tract in men. Methods Patients underwent diagnostic and therapeutic protocols according to current evidence-based practice. Efficacy assessments: voiding parameters, perineal pain, International Prostate Symptom Score (IPSS), digital rectal examination (DRE). Adverse events and patient compliance were recorded throughout the study. Results One hundred eighty patients were enrolled, mean age 52 ± 14.97. Most frequent diagnosis: nonbacterial prostatitis (85 %). All patients completed visits 1 and 2. All patients were treated with beclomethasone dipropionate (BDP) suppositories, 136/180 also withSerenoa repens (SR) extract. Antibiotics were rarely required. 162/180 patients presented clinically significant improvements and terminated treatment. Mean change vs. baseline in voiding frequency: −3.55 ± 2.70 n/day in patients taking only BDP and −3.68 ± 2.81 n/day in those taking both BDP and SR (P <.0001 in both groups). Uroflowmetry improved significantly; change from baseline 3.26 ± 5.35 ml/s in BDP only group and 5.61 ± 7.32 ml/s in BDP + SR group (P = 0.0002 for BDP, P <.0001 for BDP + SR). Urine stream normal in 35 % of patients at visit 1 and 57.22 % of patients at visit 2. Mean change in perineal pain, on 0–10 VAS, −0.66 ± 2.24 for BDP only group (P = 0.0699) and −1.37 ± 2.40 for BDP + SR group (P <.0001). IPSS increased at visit 2. No adverse events were reported. For all parameters, none of the comparisons between groups was found to be statistically significant. Conclusion This study confirmed the drug's good safety profile. We also observed an improvement in the main storage symptoms and clinical findings associated with lower urinary tract inflammation in patients treated with beclomethasone dipropionate suppositories.